A criação do Centro de Educação e Cultura Indígena (CECI) e a educação infantil indígena na aldeia Krukutu - Ferreira, Edna (2012)
This research analyzes the indigenous infant school education in the village called Krukutu, Guarani Mbya, located in the neighborhood of Parelheiros, south zone of São Paulo through the implementation of the CECI (Centre for Indigenous Education and Culture). The objective was to examine the challenges in the search for a different and intercultural education, as well as possible contributions to non-indigenous school education. The analysis is based on the notion of "frontier" in the social and pedagogical understanding it as a space for contact and exchange between populations where knowledge and traditions are able to be strengthened, rethought and reinterpreted, as well as space culture in which oral and written language meet or not with the possible disclosure of ethnic differences and ways of being and living. To perform this analysis was located the relationship between indigenous education and the standard school education, focusing on early childhood education, the historical process of the creation of CECIS, its objectives and organization, the construction of a curriculum design and the practices applied by CEII (Center Indigenous Early Childhood Education), linked to CECI Krukutu based on conceptions of child, education and educator of Guarani Mbya Krukutu village people. The survey interviews were done with community leaders, parents, children and employees that work in Krukutu CECI. Other sources were selected from documents relating to indigenous education, indigenous infant school education and non-indigenous, the pedagogical project and CECI's regiment. Through the analysis of the interviews was possible to observe the importance given to education by all indigenous school children, school, and the interest that it be strengthened, with suggestions for this to occur